2012
DOI: 10.2965/jwet.2012.437
|View full text |Cite
|
Sign up to set email alerts
|

Production of Chloro-5-hydroxy-2-nitrobenzoic Acid through Chlorination of 3-Methyl-4-nitrophenol, a Typical Hydrolysate of Fenitrothion

Abstract: Fenitrothion [O, O-dimethyl O-(3-methyl-4-nitrophenyl)phosphorothioate], a typical organophosphorus pesticide, is widely used as an insecticide in Japan. In this study, 3-methyl-4-nitrophenol (3M4NP), which is a typical hydrolysate of fenitrothion, was focused as a possible mutagen precursor because it is reported as a common contaminant in raw water for water works, and is capable of forming mutagens when it is chlorinated in water works. In order to examine molecular formulae of mutagens produced from 3M4NP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Bade et al utilized LC-HRMS to screen pharmaceuticals and illicit drugs in wastewater and surface water, identifying many compounds including irbesartan, valsartan, benzoylecgonine, caffeine, and so on [82]. Takanashi et al focused on 3-methyl-4-nitrophenol (3M4NP), a typical hydrolysate of fenitrothion, and proposed that chloro-5-hydroxy-2-nitrobenzoic acid was possibly generated as a chlorination product of 3M4NP [83]. Kondo et al monitored pesticides and their transformation products in water environments utilizing LC-MS/MS [84].…”
Section: Approach Required To Solve the Problemmentioning
confidence: 99%
“…Bade et al utilized LC-HRMS to screen pharmaceuticals and illicit drugs in wastewater and surface water, identifying many compounds including irbesartan, valsartan, benzoylecgonine, caffeine, and so on [82]. Takanashi et al focused on 3-methyl-4-nitrophenol (3M4NP), a typical hydrolysate of fenitrothion, and proposed that chloro-5-hydroxy-2-nitrobenzoic acid was possibly generated as a chlorination product of 3M4NP [83]. Kondo et al monitored pesticides and their transformation products in water environments utilizing LC-MS/MS [84].…”
Section: Approach Required To Solve the Problemmentioning
confidence: 99%
“…Fipronil yields its sulfone or additional forms in chlorine treatment (Teerlink et al, 2017). Fenitrothion is transformed into its oxon form and other fragments by chlorine treatment (Takanashi et al, 2012). Chlorine treatment also decomposes bensulfuron methyl (Hu et al, 2015) and halosulfuron methyl (Wang et al, 2015).…”
Section: Detected Concentrations Of Pesticidesmentioning
confidence: 99%
“…C5H2NBA is thought to be a major contributor to the mutagenicity observed after chlorination of 3M4NP solutions (i.e., it is thought to be a mutagenic CTP) (Takanashi et al 2012). In the present study, we focused Effect of UV irradiation time on mutagenicity intensity (MI 500 ) of 3-methyl-4-nitrophenol solutions before and after chlorination: AOP (white circles) and AOP/Cl (black circles), without (−S9mix) and with (+S9mix) metabolic activation in the Ames assay.…”
Section: Mutagenicity Derived From Cotpsmentioning
confidence: 99%
“…In fact, Kishida et al (2010) reported that a 3M4NP solution became mutagenic after the addition of free chlorine, indicating that 3M4NP is transformed into a mutagenic compound or compounds during chlorination. Takanashi et al (2012) reported that chloro-5-hydroxy-2-nitrobenzoic acid (C5H2NBA) is largely responsible for the mutagenicity induced by chlorination of 3M4NP solutions. Moreover, Kishida et al (2010) reported that the mutagenicity of a chlorinated 3M4NP solution is much higher than that of a chlorinated fenitrothion solution at the same molar concentration.…”
Section: Introductionmentioning
confidence: 99%